Use the intermediate value theorem to show that f(x) = -x^4 + 3x^3 - 2x + 1 has zero between 2 and 3
f(a) = -(2)^4 + 3(2)^3 - 2(2) + 1
= -16 + 24 - 4 + 1
= -20 + 25
f(b) = -(3)^4 + 3(3)^3 - 2(3) + 1
= - 81 + 81 - 6 + 1
= -87 + 82
Is this correct?
Dear Plato,Rafael Almeida, with all due respect, I don’t think that you have the experience to correct me. What I clearly was trying to do was to guide the poster to an understanding of his/her own
I am sorry, I never meant to. Now I see what happened, I mistook your username for mwok's. I though the username Plato started the topic.
To clarify things, the tip was to mwok. And surely, I don't have neither the experience nor the reputation to correct anybody in here, particularly a poster like you. I'm more a learner than a tutor and I hope to help where I can while I work out my learning process with the help of people like you.
So, again, sorry for the misunderstanding.